Early rehabilitation after hospital admission for road trauma using an in-reach multidisciplinary team: a randomised controlled trial. (September 2017) - Wu, Jane; Faux, Steven G; Estell, John; Wilson, Stephen; Harris, Ian; Poulos, Christopher J; Klein, Linda
Objective: To investigate the impact of an in-reach rehabilitation team for patients admitted after road trauma. Design: Randomised control trial of usual care versus early involvement of in-reach rehabilitation team. Telephone follow-up was conducted by a blind assessor at three months for those with minor/moderate injuries and six months for serious/severe injuries. Setting: Four participating trauma services in New South Wales, Australia. Subjects: A total of 214 patients admitted during 2012-2015 with a length of stay of at least five days. Intervention: Provision of rehabilitation services in parallel with ward based therapy using an in-reach team for the intervention group. The control group could still access the ward based therapy (usual care). Main measures: The primary outcome was acute length of stay. Secondary outcomes included percentage requiring inpatient rehabilitation, function (Functional Independence Measure and Timed Up and Go Test), psychological status (Depression Anxiety and Stress Score 21), pain (Orebro Musculoskeletal Pain Questionnaire) and quality of life (Short Form-12 v2). Results: Median length of stay in acute care was 13 days (IQR 8-21). The intervention group, compared to the control group, received more physiotherapy and occupational therapy sessions (median number of sessions 16.0 versus 11.5, P =0.003). However, acute length of stay did not differ between the intervention and control groups (median 15 vs 12 days, P =0.37). There were no significant differences observed in the secondary outcomes at hospital discharge and follow-up. Conclusion: No additional benefit was found from the routine use of acute rehabilitation teams for trauma patients over and above usual care.